Challenges and Opportunities: Cattle / Sheep Farming Business in the City : Case Study of Good Cattle in Depok City - Lastro, Djano; Windarko, Windarko; Maharani, Putri; Yusup, Tiara Yuristina; Mala, Chajar Matari Fath; Iskandar, Yusuf; Dewi, Cynthia Sari (West Science Business and Management, 2024)
This research investigates the challenges and opportunities associated with cattle and sheep farming businesses in urban environments, particularly emphasizing outstanding cattle farming enterprises in Depok. The study aims to provide an in-depth analysis of these businesses' strategies to address existing challenges and leverage potential opportunities. By exploring the innovative practices and adaptive measures employed by urban livestock farmers, this research seeks to uncover effective methods for breeders to navigate market dynamics, enhance operational efficiencies, and sustainably improve the productivity and quality of their livestock operations. Focusing on success stories from Depok, the study highlights how exemplary cattle farming businesses have thrived despite the constraints of an urban setting. It examines the role of technology, community engagement, and sustainable farming practices in driving their success. The findings offer valuable insights and recommendations for breeders, policymakers, and stakeholders on fostering a resilient and prosperous urban livestock farming sector. Ultimately, this research contributes to the broader discourse on urban agriculture, providing lessons on sustainable growth and productivity enhancement in urban livestock farming.